Evaluating the impact of public financial support on innovation activities of European Union enterprises: Additionality approach - Małgorzata Lewandowska; Marzenna Anna Weresa; Małgorzata Rószkiewicz (International Journal of Management and Economics, 2022)
The study aims at estimating the effects of support for research and development and innovation from the European Union (EU) budget for boosting innovation in European enterprises, using input, output, and behavioral additionality approach. The study is based on microdata of the Community Innovation Survey 2012-2014, covering a sample of 98,809 enterprises from 14 EU countries. The direct and indirect relationships between the variables were studied using path analysis. For the whole sample, three additionality dimensions were confirmed; however, the result differs across EU member states. Multi-additionality of EU grants was confirmed only for Spain; in eight EU countries, input and behavioral additionality were proved, and in two, only behavioral additionality was found. This leads to the conclusion that the potential of EU support is not fully exploited, in particular in Central and Eastern European countries, and there is room for improvements with regard to policy design and implementation.
Keywords: C50; L2; O3; 650; additionality of public support; European Union; innovation; innovation policy; R&D grants